An Evaluation of English Textbook Published by The Ministry of Education And Culture - Santihastuti, Asih; Nursalsabilla, Nastiti Kurniasari; Sukmaantara, I Putu (EFL Education Journal, 2023)
This study evaluated the tenth grade students’ English textbook publishedby the Ministry of Education and Culture of the Republic of Indonesia 2016retrospectively. It had purposes to know whether or not the textbook has all thecriteria expected in the adapted version of ELT Textbook Evaluation Checklistproposed by Mukundan and Nimehcisalem (2015); as well as to know how thistextbook can be improved. Three tenth grade English teachers in three differentsenior high schools in Jember were selected as the evaluators to give their opinionabout the content of the textbook. The checklist result was counted to look for theaverage score from each criterion; and the result of the interview was analyzed usinga procedure of analyzing qualitative data adapted from Creswell (2012). The findingsrevealed that this textbook has all the criteria expected in the checklist with the totalaverage score of 2.95 (high usefulness); but there were some improvements neededdealing with suitability to learners, general content, grammar, pronunciation,exercises, reading, methodology, and listening. Therefore, 10 suggestions weregiven by the evaluators to overcome the problems in those criteria.